The impact of childhood acute rotavirus gastroenteritis on the parents’ quality of life: prospective observational study in European primary care medical practices - Domingo, Javier Diez (BioMed Central, 2012)
BACKGROUND: Rotavirus (RV) is the commonest cause of acute gastroenteritis in infants and young children worldwide. A Quality of Life study was conducted in primary care in three European countries as part of a larger epidemiological study (SPRIK) to investigate the impact of paediatric rotavirus gastroenteritis (RVGE) on affected children and their parents. METHODS: A self-administered questionnaire was linguistically validated in Spanish, Italian and Polish. The questionnaire was included in an observational multicentre prospective study of 302 children aged <5 years presenting to a general practitioner or paediatrician for RVGE at centres in Spain, Italy or Poland. RV infection was confirmed by polymerase chain reaction (PCR) testing (n = 264). The questionnaire was validated and used to assess the emotional impact of paediatric RVGE on the parents. RESULTS: Questionnaire responses showed that acute RVGE in a child adversely affects the parents’ daily life as well as the child. Parents of children with RVGE experience worry, distress and impact on their daily activities. RVGE of greater clinical severity (assessed by the Vesikari scale) was associated with higher parental worries due to symptoms and greater changes in the child’s behaviour, and a trend to higher impact on parents’ daily activities and higher parental distress, together with a higher score on the symptom severity scale of the questionnaire. CONCLUSIONS: Parents of a child with acute RVGE presenting to primary care experience worry, distress and disruptions to daily life as a result of the child’s illness. Prevention of this disease through prophylactic vaccination will improve the daily lives of parents and children.